PSXI-18 Effects of Glucose Infusion on Expression of Genes Related to Amino Acid Metabolism in Muscle and Mammary Glands of Lactating Dairy Cows. (7th December 2018) - Pot, L; Li, B; Laforest, R; Curtis, R; Kim, J; Seymour, D; Cant, J; Doelman, J
Abstract: Milk protein yield (MPY) responses to dietary carbohydrates, particularly glucose, are partially regulated by protein synthetic pathways such as mechanistic target of rapamycin (mTORC1) and the integrated stress response (ISR) network. However, changes in these pathways have not been observed in response to prolonged glucose supplementation, despite observed changes in MPY. To determine if gene expression could identify alternative mechanisms of the MPY response to glucose, mammary and muscle biopsies were analyzed from two separate trials in which dairy cattle received supplemental glucose. In experiment 1, cows (n = 12) received 0 or 1 kg/d glucose I.V. in a switchback design. In experiment 2, cows (n = 5) received 0, 1.1, or 2.2 kg/d of glucose via abomasal infusion in a Latin square design. In both trials, glucose infusion did not affect DMI but increased milk and lactose yields. Glucose infusion significantly increased MPY 63 g/d in experiment one, and tended ( P = 0.15) to increase MPY 82 g/d in experiment two. In mammary tissue, expression of genes related to protein translation, cell turnover, and cell differentiation were unaffected by infusion treatments ( P > 0.15). Longissimus dorsi tissue was analyzed to determine if changes in muscle metabolism could support or interfere with glucose effects on milk protein synthesis in the mammary glands. Despite evidence of an insulin/glucose response in expression of genes related to glucose metabolism, no significant changes in genes related to protein turnover or amino acid metabolism were detected in skeletal muscle ( P > 0.15). Overall, our findings suggest that glucose-induced changes in milk and component yields are not under transcriptional control of secretory cell activity or turnover, nor are there significant changes in muscle gene expression that support changes in amino acid supply for milk protein synthesis in the mammary glands.